Dielectric relaxation analysis of chemical solid electrolyte lithium aluminum titanium phosphate - Zangina, Tasiu; Hassan, Jumiah; Matori, Khamirul Amin; Azis, Raba`ah Syahidah; Ndikilar, Chifu Ebenezer; Naning @ Zin, Fatin Hana (Knowledgia Scientific, 2018)
Background and Objective: The study of relaxation and ionic conductivity behavior of conducting materials comes to be a significant area of research interest due to their potential application in electronic devices. The objective of the present study was to investigate the dielectric relaxation property of lithium aluminum titanium phosphate Li1.5Ti1.5 (PO4)3 with NASICON-type structure. Materials and Methods: The material was prepared by conventional solid state technique, while characterization was carried out using X-ray powder diffraction (XRD) and impedance spectroscopy (IS) analysis technique. The structure and phase composition of the material was indicated by XRD analysis. Temperature and frequency dependence of AC conductivity and dielectric relaxation behavior were obtained at different temperatures from 30-280°C within the frequency range of 40 Hz to 1 MHz. Results: The AC conductivity was observed to be frequency-independent in the low frequency region and frequency-dependent at higher frequency region (10 KHz to 1 MHz). For dielectric permittivity analysis, the dielectric constant ε’ and dielectric loss ε” were found to increase at low frequency and decrease as frequency increased at all temperatures. The calculated AC conductivity of 6.61×10–4 (Ωm)–1 was observed at room temperature (30°C). The relaxation energy (Ea) of 0.21 eV was obtained from electrical modulus formalism. Conclusion: The synthesized sample Li1.5Ti1.5Al0.5 (PO4)3 indicated two relaxation processes, in each relaxation the peaks shifted to higher frequency as the measuring temperature increased.